KONTRIBUSI SPATIAL REASONING DAN WORKING MEMORY TERHADAP PRESTASI MATEMATIKA SISWA SMP - Dewi Komalasari, Junita; Yulinda Sari, Desi; Khaironi, Nispatul; Endriana, Neny; Supiyati, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the contribution of spatial reasoning and working memory to junior high school students’ mathematics achievement. Mathematics learning at the secondary level requires not only procedural skills but also cognitive abilities that support visualization, information processing, and problem solving. Many students experience difficulties when mathematical tasks demand abstract thinking and multi-step reasoning. These difficulties are often related to limitations in spatial reasoning and working memory. The purpose of this research is to analyze the partial and simultaneous contributions of spatial reasoning and working memory to students’ mathematics achievement. A quantitative approach with an ex post facto design was employed. The study was conducted at MTs Mualimin NWDI Pancor during the 2025/2026 academic year. The population consisted of all eighth-grade students, and a sample of one hundred students was selected using simple random sampling. Data were collected through spatial reasoning tests, working memory tests, and mathematics achievement tests. The instruments were validated by experts and tested for reliability. Data analysis included descriptive statistics, assumption tests, and multiple linear regression. The results indicate that spatial reasoning has a positive and significant effect on mathematics achievement, while working memory does not show a significant partial effect. However, both variables together contribute meaningfully to students’ mathematics achievement. These findings suggest that mathematics learning should emphasize the development of spatial reasoning skills alongside strategies that help students manage cognitive load. Integrating visual representations and structured problem-solving activities may enhance learning outcomes and support students’ mathematical understanding.